Sampoerna Retail Community Program Corporate Social Responsibility Communication Strategy in Marga Mulya, Bekasi City - Nurul Mukharomah; Retno Putra; Wulan Furrie Lenggana (Formosa Journal of Sustainable Research, 2023)
The CSR program is a company commitment to support the creation of sustainable development. PT HM Sampoerna Tbk is one of the companies in Indonesia that implements a CSR program. The CSR program they run is the Sampoerna Retail Community (SRC), which aims to foster partner grocery stores to become more innovative and competitive. In this research stage, the literature review was carried out with a systematic approach, by referring to various sources available in various research databases. After the screening process, 7 articles were selected to proceed to the next stage. The results of the research are that PT HM Sampoerna Tbk has successfully implemented the Corporate Social Responsibility (CSR) program with a mature and effective communication strategy. The steps taken by the company, starting from setting clear goals, actively communicating with various stakeholders, to involving the community in planning and implementing programs, have had a significant positive impact